2007
DOI: 10.1186/1471-2350-8-42
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of genetic screening in families of patients with germline MUTYH mutations

Abstract: Background: MUTYH associated polyposis (MAP) is an autosomal recessive inherited disorder. Carriers of bi-allelic MUTYH germline mutations have a risk of approximately 60% to develop colorectal carcinoma (CRC). In the general population about 1.5% is a heterozygous MUTYH mutation carrier. Children of MAP patients have an increased risk of inheriting two MUTYH mutations compared to the general population, implicating an increased risk for developing CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Different variants of the MUTYH gene can affect the protein function and hence the DNA repair capacity that is tightly linked to cancer development. Biallelic germline mutations in the MUTYH lead to MUTYH associated polyposis (MAP) and provide a significant risk for colorectal cancer [24]. Different studies supported the role of MUTYH in colorectal adenoma and carcinoma pre-disposition [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different variants of the MUTYH gene can affect the protein function and hence the DNA repair capacity that is tightly linked to cancer development. Biallelic germline mutations in the MUTYH lead to MUTYH associated polyposis (MAP) and provide a significant risk for colorectal cancer [24]. Different studies supported the role of MUTYH in colorectal adenoma and carcinoma pre-disposition [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Although carriers of biallelic MUTYH mutations have a 60% risk to develop CRC [24] it is now clear that some genes which cause autosomal recessive cancers predisposition are related to fairly increased risk of adult cancer in monoallelic carriers [25]. Such monoallelic mutations may be strongly related to cancer when combined with other genes mutations [26] or carcinogen exposure [27] and they also can influence genetic pathways in CRC [19].…”
Section: Introductionmentioning
confidence: 99%
“…One‐third of the respondents do not recommend regular upper gastrointestinal tract surveillance. The currently available evidence is insufficient to endorse or refute the recommendation, but the reported association of MAP with duodenal polyposis and other extracolonic features typical of FAP makes upper gastrointestinal surveillance not unreasonable, at least until more definitive data are available 11,19 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown biallelic MUTYH mutations in 26% to 29% of patients with 10–100 polyps,7 and in these families it is cost effective to perform genetic screening, since 2% of the normal population is heterozygous for an MUTYH mutation; a child of a biallelic mutation carrier has a 1% chance of inheriting two mutated MUTYH alleles 15. However, the true prevalence of MAP remains unclear, and the phenotypic characteristics are still being determined.…”
Section: Mutyh-associated Adenomatous Polyposismentioning
confidence: 99%